Curriculum for Society-Engineer Interaction Studies - Wakhlu, O. N. (Journal of Engineering Education Transformations, 1992)
Engineering is a people serving profession. What the engineer accomplishes through his work affects society in manifold ways. The engineers are change agents of the society as well as managers of change. Inspite of this reality, the engineers' education and training is inadequate to the extent that it does not enable them to play their role effectively in this respect. This has forced the engineer into the position of a second fiddle in decision making related to major societal coners. The paper discusses these issues and proposes addition of new courses in engineering curricula which have relevance to society-engineer interaction and other interrelated aspects of man-management facets of engineers' work. It is concluded that this proposed new curriculum will bring about a dynamic change in the professional integrity and leadership role of the engineers in society. In the present scenario all the benefits of the work done by engineers is taken for granted, whereas, a lot of blame is put on them for spoiling the world and its environment. It is for engineers to remedy the situation through changes in education and training in the colleges, as well as through continuing education throughout their lifetime.